Leadership and Emotions Lessons from Sant’Ignazio de Loyola and Martha Naussbaum - Caggiano, Valeria; Ragusa, Antonio (Studi sulla Formazione/Open Journal of Education, 2022)
The article proposes to highlight the link between leadership and emotions starting from the Ignatian lesson and Nussbaum’s lesson. The leadership of discernment, characterised by Saint Ignatius’ pedagogy, is proposed in its formative practices and in the possibility of coexisting in the practices of working and professional life. Relational leadership, suggested by the reading of capabilities and the factors that regulate emotions, also becomes an engine of social and work transformation. The training practices that have the Humanistic Approach as a method find in the proposed Lessons a solid tool to deal with a liquid theme.